Stone material in the archaeological site oftiddis and its architectural andartistic uses in various facilities and buildings in the roman period - boukecira, yousra; Boudraa, Sufyan (The Algerian Historical Journal, 2026)
Stones are considered the main material that man came into contact with and marked his fingerprints on, and it is the main component of any archaeological site, rather it represents the nucleus of its first formation, because stones equal construction and stability. Where the ancient man excelled in his exploitation of the material of stones of all kinds through creativity in the process of carving on them, so they performed many functions in various shapes and sizes and represented the main source for looking at the arts of architecture in the ancient period, and since the stones occupy the space of the archaeological site as a whole, their purpose and how to deal with them and work differ According to the function that it will perform in the building or in every part of the site, this is what we will deal with in this article by highlighting aspects of the art of carving on stones in the archaeological site of Tiddis and its architectural uses, in which the sculptor took into account the aesthetic and technical at one time and mixed both at other times.